2015
DOI: 10.1016/j.juro.2014.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of Renal Cell Carcinoma with Belinostat and 5-Fluorouracil: A Role for Oxidative Stress Induced DNA Damage and HSP90 Regulated Thymidine Synthase

Abstract: In combination with 5-fluorouracil the targeted inhibitor of histone deacetylase synergistically inhibited renal cancer cell growth by the blockade of thymidylate synthase induction and the induction of reactive oxygen species mediated DNA damage in vitro and in vivo. Our results suggest that combined treatment with belinostat and 5-fluorouracil may represent a promising new approach to renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…TS expression is closely correlated with the response to both 5-FU and HDAC inhibitors in several cancer cell lines [25][26][27][28]. In the present study, TS was upregulated by 5-FU exposure alone, whereas SAHA downregulated TS expression in the presence or absence of 5-FU in a dose-dependent manner in HCC cell lines.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…TS expression is closely correlated with the response to both 5-FU and HDAC inhibitors in several cancer cell lines [25][26][27][28]. In the present study, TS was upregulated by 5-FU exposure alone, whereas SAHA downregulated TS expression in the presence or absence of 5-FU in a dose-dependent manner in HCC cell lines.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to histones, HDAC inhibitors deacetylate many nonhistone proteins including heat shock proteins (HSPs). HDAC inhibitors upregulate the expression of acetylated HSP-90, which is an essential member of the HSP family [26,37]. HDAC6 is mostly responsible for HSP-90 deacetylation, which preserves its function [22,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35] It has been reported that oxidative stress play a significant positive effects on the growth and progression of RCC. [36][37][38][39] Strong anti-oxidants are reported to have strong anticancer abilities.…”
Section: Discussionmentioning
confidence: 99%